2020
DOI: 10.1039/d0ra05692h
|View full text |Cite
|
Sign up to set email alerts
|

Application status and technical analysis of chitosan-based medical dressings: a review

Abstract: Chitosan has wide applications in the field of medical dressings due to its good biomedical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 132 publications
1
23
0
Order By: Relevance
“…Some scholars believe that the antibacterial properties of chitosan increase with the increase of its molecular weight [ 179 ]. Zheng et al, showed that for chitosan with a molecular weight of less than 300 kDa, as the molecular weight increases, the antibacterial effect on S. aureus was enhanced, but the antibacterial effect on E. coli was weakened [ 180 ].…”
Section: Antibacterial Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars believe that the antibacterial properties of chitosan increase with the increase of its molecular weight [ 179 ]. Zheng et al, showed that for chitosan with a molecular weight of less than 300 kDa, as the molecular weight increases, the antibacterial effect on S. aureus was enhanced, but the antibacterial effect on E. coli was weakened [ 180 ].…”
Section: Antibacterial Mechanismsmentioning
confidence: 99%
“…However, traditional wound dressings made of cotton or gauze not only lack necessary antibacterial properties but also need to be changed frequently to keep the wound clean, which may cause secondary injury to the wound. Research indicates that the ideal wound dressing should act as a microbial barrier without affecting gas exchange [ 179 ]. The application of electrospinning in the field of wound dressing has the following advantages: (1) the high gas permeability provided by the high porosity of the electrospun fiber; (2) the high absorption caused by the high specific surface area of the fiber; (3) the biocompatibility and antibacterial properties of electrospinning materials.…”
Section: Application Fieldsmentioning
confidence: 99%
“…The damaged skin would endanger human health and even human life [3]. Currently, we need to use skin substitutes and medical wound dressings to repair the damaged skin [4]. At present, most of the medical dressing materials were synthetic polymers, which were not degradable, or the degradation products were toxic and easy to cause secondary damage to the damaged skin [5].…”
Section: Introductionmentioning
confidence: 99%
“…Scaffold materials mainly include inorganic materials, natural polymer materials and synthetic polymer materials. [14][15][16][17][18][19][20][21][22] Inorganic materials such as tricalcium phosphate, hydroxyapatite, coral and so on, which are generally only suitable for bone tissue engineering, are difficult to process and have high brittleness. 14,15 Natural polymer materials such as collagen, hyaluronic acid, chitosan and so on have uncontrollable degradation rate in vivo, poor strength and processing performance and bad batch repeatability.…”
Section: Introductionmentioning
confidence: 99%